Ide Kreatif Konten Instagram @cretivox untuk Mempertahankan Eksistensi sebagai Media Kreatif - Husna, Nurul Fadillah Hul; Wahdiyati, Dini; Maududi, Mukhlish Muhammad (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This study examines the creative content ideas on Instagram @cretivox in maintaining its existence as a creative media amid the increasingly competitive digital industry. The problem addressed in this research is how the creative ideas implemented in the content of Instagram @cretivox contribute to sustaining Cretivox's existence as a creative media. The purpose of this research is to analyze the creative elements used in Cretivox’s content and to understand the role of content in building engagement with the audience. This study uses a qualitative approach with a qualitative content analysis method. Data collection techniques include observation, in-depth interviews, and documentation. The results show that Cretivox consistently applies creative content ideas that reflect the four functions of media according to Denis McQuail: information, correlation, continuity, and entertainment. This implementation is evident through the use of hashtags as brand identity, engaging visuals, a distinctive tone of voice, and relevant content themes that contribute to building strong brand positioning and maintaining its existence as a creative media platform.